PENGEMBANGAN LAHAN BASAH SUB-OPTIMAL : PERTUMBUHAN Moringa Oleifera (L) PADA TANAH SULFAT MASAM YANG DIBERI BAHAN AMELIORAN - Rabiatul Wahdah; Antar Sofyan; Aswarin Aswarin (Universitas Lambung Mangkurat, 2022)
Moringa is a plant that has a myriad of benefits, either to fulfill human nutrition or as an ingredient used for animal feed. Information to the public is still very minimal about the benefits of this Moringa plant, and it also requires a large area of land to cultivate it. Acid sulphate land is a land that is underutilized as agricultural crop cultivation because it has a serious limiting factor, but has the potential to cultivate Moringa plants, because Moringa plants are tolerant of high soil acidity. This high soil acidity can be overcome by the addition of ameliorant materials in the form of husk ash and empty oil palm fruit bunches (OPEFB). Besides being able to improve the physical and chemical properties of the soil, ameliorant is expected to improve soil fertility in acid sulfate soils. This research was carried out by taking soil in the Barito Kuala area, precisely in the Tabukan sub-district as a polybag scale planting medium, this study used a factorial completely randomized completely randomized design method. The results of soil sample analysis showed that the characteristics of acid sulfate soils were very low, and had very high levels of toxic elements such as Fe and Al. While the results of the analysis of OPEFB compost the chemical element values ranged from high to very high so it was very good for application to acid sulfate fields. The treatment of OPEFB compost and husk ash affected the growth of the number of Moringa plant shoots with the best treatment being 20 ton.ha-1 and husk ash 10 ton.ha-1.